Drop out prediction in sport centres. Definition of models and reproducibility (Predicción de bajas de clients en centros deportivos. Definición de modelos y reproducibilidad) - Clavel San Emeterio, Iván; García-Unanue, Jorge; Iglesias-Soler, Eliseo; Gallardo, Leonor; Felipe, José Luis (Retos, 2020)
Abstract. Purpose: One of the main problems detected in the sport centre field is abandonment of physical activity by members. The aim of this estudy is to evaluate the reproducibility of predictive models of abandonment in sports centres, based on information collected through access control and the Customer Relationship Management system. Method: Monthly data corresponding to the actual behaviour of of two sport centres in Spain were recorded over the course of one year (12,545 members). Based on these variables, two predictive models were designed using the absence or permanence in the centre as an independent variable. Subsequently, the regression formula obtained was applied on all members of the same sports centres a year later (12,986 members), checking the effectiveness and reproducibility of the model. Results:. Logistic regression models based on customer historical behaviour were useful to predict abandonment. The effectiveness of the models was around 70% a year after. Conclusions: The segmentation of users based on the likelihood of drop out and the identification of behaviour variables that predict such drop out and the confirmation of the effectiveness of the predictive model, can help to optimize the design of loyalty strategies to prevent the abandonment in sport centres.Resumen.  Objetivo: El abandono de la práctica deportiva por parte de clientes en centros deportivos es uno de los principals problemas en el sector. El objetivo de este estudio es evaluar la reproducibilidad de modelos predictivo de abandono en centros deportivos, basados en información recogida a través del control de accesos y el sistema Customer Relationship Management. Método: Se recopiló comportamientos mensuales de los clientes de dos centros deportivos en España durante un año (12,545 members). En base a dichas variables se diseñaron dos modelos predictivos utilizando la baja o permanencia en el centro como variable independiente. Posteriormente, se aplicó la formula de regression obtenida sobre todos los miembros de los mismos centros deportivos un año después (12,986 members), comprobando la efectividad y reproducibilidad del modelo. Resultados: Las estimaciones de regression logística fueron útiles para predecir el abandon en los centros deportivos. Además, reproduciendo el mismo modelos en una muestra diferente se consiguió aproximadamente un 70% de efectividad. Conclusiones: La segmentación de usuarios en base a la probabilidad de baja y la identificación de variables predictivas de dicha baja pueden optimizar el diseño de estrategias de prevención de abanadono en centros deportivos.